Comorbidities Coma Scale (CoCoS): Linguistic and Cultural Adaptation of the Russian-Language Version - N. A. Suponeva; M. A. Piradov; Yu. V. Ryabinkina; Dj. G. Yusupova; A. A. Zimin; O. A. Kirichenko; N. G. Buzgan; K. A. Yatsko; D. V. Sergeev; A. B. Zaytsev; L. A. Legostayeva; E. G. Yazeva; et al. (Общая реаниматология, 2022)
Identification of complications and control of comorbidities are essential in monitoring the patients with chronic disorders of consciousness and predicting their outcomes. The researchers of the Department of Biotechnological and Applied Clinical Sciences of the University of L'Aquila (Italy) developed the Comorbidities Coma Scale (CoCoS) for a comprehensive assessment of such patients. Lack of an officially validated version of the scale hampers its use in Russia, while using versions which have not been completely validated prevents clinicians from obtaining reliable results when examining patients with chronic disorders of consciousness.   Aim. To develop the official Russian language version of the Comorbidities Coma Scale, considering various linguistic and cultural parameters, as a part of the 1st stage of the validation study.   Material and methods. The first stage of validation was completed: direct and reverse translation of the scale was performed by two independent medical translators. The translated version was assessed by an expert board including an expert translator, neurologists, and critical care specialists. Pilot test and two meetings of the expert board, before and after testing, were arranged to assess the results and approve the final Russian version of the scale.   Results. During the first meeting of the expert board, corrections were made in the Russian language version of the scale in terms of language and cultural adaptation. Pilot testing was carried out based on the inclusion and exclusion criteria. The researchers had no difficulties in understanding and interpreting the instructions for the scale. The second meeting of the expert board was held thereupon, and the final version of the Russian language version of the scale was adopted, which is available on the website of the Center for Validation of Health Status Questionnaires and Scales of the Research Center of Neurology.   Conclusion. The first stage of validation, i. e., linguistic and cultural adaptation, was carried out at the Research Center of Neurology (Moscow, Russia). For the first time, the Russian version of the scale for assessing comorbidities in patients with chronic disorders of consciousness was presented and approved for the practical use. The future publications will address the psychometric results of the scale such as sensitivity, validity, reliability.